2013
DOI: 10.1590/s1517-83822014005000017
|View full text |Cite
|
Sign up to set email alerts
|

Cashew apple juice as microbial cultivation medium for non-immunogenic hyaluronic acid production

Abstract: In this work, natural cashew apple juice was used as cultivation medium as an alternative to substitute brain heart infusion medium. The effect of aeration and juice supplementation with yeast extract on the production of hyaluronic acid in batch fermentation was also investigated. Similar levels of cell mass were obtained in inoculum using cashew apple juice supplemented with yeast extract or the conventional brain heart infusion medium. Fermentation in Erlenmeyer flasks produced low biomass and hyaluronic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Because molasses has a low total nitrogen content, supplementation with yeast extract is necessary to achieve an ideal carbon/nitrogen ratio. Lancefield group A and C streptococci bacteria require complex nutrients due to their limited ability to synthesize specific amino acids and vitamins [19,35]. Previous studies suggested that certain essential amino acids cannot be synthesized from an inorganic nitrogen source, because hyaluronic acid production in this medium is very low [36,37].…”
Section: Effect Of Pretreated Sugarcane Molasses and Yeast Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…Because molasses has a low total nitrogen content, supplementation with yeast extract is necessary to achieve an ideal carbon/nitrogen ratio. Lancefield group A and C streptococci bacteria require complex nutrients due to their limited ability to synthesize specific amino acids and vitamins [19,35]. Previous studies suggested that certain essential amino acids cannot be synthesized from an inorganic nitrogen source, because hyaluronic acid production in this medium is very low [36,37].…”
Section: Effect Of Pretreated Sugarcane Molasses and Yeast Extractmentioning
confidence: 99%
“…Vázquez et al [14,17] reported the successful use of marine peptones from fishing byproducts for hyaluronic acid production. Agricultural resource derivatives such as cashew apple juice, cheese whey, and soy protein were also studied [11,18,19]. For instance, Amado et al [20] saved 70 % of the nutrient cost by replacing commercial peptone with cheese whey during polymer production.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy also lowered organic waste pollution. Oliveira et al [13] stated that cashew apple juice can replace brain heart infusion medium as a reliable culture medium for Streptococcus zooepidemicus fermentation for HA production. In this paper, when cheaper sucrose was used as carbon source and corn steep liquor (processing by-products of corn starch) was used as nitrogen source for Streptococcus equi JC-63 fermentation, the relative molecular weight and output of HA reached 2.72 × 10 6 Da and 4.12 g/L, respectively.…”
Section: Discussionmentioning
confidence: 99%